Dissecting the Neuronal Contributions of the Lipid Regulator NHR-49 Function in Lifespan and Behavior in C. elegans - Saebom Kwon; Kyu-Sang Park; Kyoung-hye Yoon (Life, 2023)
Although the importance of lipid homeostasis in neuronal function is undisputed, how they are regulated within neurons to support their unique function is an area of active study. NHR-49 is a nuclear hormone receptor functionally similar to PPARα, and a major lipid regulator in C. elegans. Although expressed in most tissues, little is known about its roles outside the intestine, the main metabolic organ of C. elegans. Here, using tissue- and neuron-type-specific transgenic strains, we examined the contribution of neuronal NHR-49 to cell-autonomous and non-autonomous nhr-49 mutant phenotypes. We examined lifespan, brood size, early egg-laying, and reduced locomotion on food. We found that lifespan and brood size could be rescued by neuronal NHR-49, and that NHR-49 in cholinergic and serotonergic neurons is sufficient to restore lifespan. For behavioral phenotypes, NHR-49 in serotonergic neurons was sufficient to control egg-laying, whereas no single tissue or neuron type was able to rescue the enhanced on-food slowing behavior. Our study shows that NHR-49 can function in single neuron types to regulate C. elegans physiology and behavior, and provides a platform to further investigate how lipid metabolism in neurons impact neuronal function and overall health of the organism.